2012
DOI: 10.17221/165/2011-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low oxygen and high carbon dioxide atmospheres on the formation of volatiles during storage of two sweet cherry cultivars

Abstract: Goliáš J., Létal J., Veselý O., 2012. Eff ect of low oxygen and high carbon dioxide atmospheres on the formation of volatiles during storage of two sweet cherry cultivars. Hort. Sci. (Prague), 39: 172-180.Th e aroma profi les of two sweet cherry cultivars Kordia and Vanda were investigated during storage at diff erent oxygen and carbon dioxide levels and at a low temperature using solid phase microextraction gas chromatography combined with mass spectrometry (SPME-GC-MS). Th e most abundant aroma volatiles obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Aminoacid metabolism generates aromatic, aliphatic, and branched chain alcohols, acids, carbonyls, and esters that are important to the flavour of fruit. 1-Hexanol, 3-methylbutan-1-ol and 3-methyl-2-buten-1-ol are products of the deamination of the relevant α-aminoacids through oxidation reactions that occur during aerobic storage of cherry fruit [ 29 ]. Yu et al [ 30 , 31 , 32 ] demonstrated that valine, leucine, alanine and aspartic acid can be converted to short chain carbonyls by tomato extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Aminoacid metabolism generates aromatic, aliphatic, and branched chain alcohols, acids, carbonyls, and esters that are important to the flavour of fruit. 1-Hexanol, 3-methylbutan-1-ol and 3-methyl-2-buten-1-ol are products of the deamination of the relevant α-aminoacids through oxidation reactions that occur during aerobic storage of cherry fruit [ 29 ]. Yu et al [ 30 , 31 , 32 ] demonstrated that valine, leucine, alanine and aspartic acid can be converted to short chain carbonyls by tomato extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Volatile emission from the fruit was not directly controlled in this experiment, in the absence of odor collection equipment. However, we did choose amounts of fruit that approximated similar overall volatile release rates (≤1.5 fold difference) based on previous studies for plum ( Pino and Quijano 2012 ), cherry ( Goliáš et al. 2012 ; Hayaloglu and Demir 2016 ) and raspberry ( Malowicki et al.…”
Section: Methodsmentioning
confidence: 99%
“…High CO 2 treatment during storage maintained the quality and decreased the respiration rate of sweet cherries (Wang et al, 2015; Wang & Long, 2014) and these have a higher tolerance to CO 2 than most stone fruit (Wani et al, 2014). However, most such studies have focused on antioxidant capacity and fruit quality (Goliáš et al, 2012; Tian et al, 2004; Wang et al, 2015; Wang & Long, 2014), with few studies on respiratory metabolism. Therefore, the aim of this study was to investigate quality changes, aerobic respiration, anaerobic respiration, and cell membrane integrity in two cultivars of sweet cherries following exposure to high CO 2 during storage at 0°C for 60 d.…”
Section: Introductionmentioning
confidence: 99%